A COMPARISON OF THE EVOLUTION OF DIAMONDIFEROUS QUARTZ-RICH ROCKS FROM THE SAXONIAN ERZGEBIRGE AND THE KOKCHETAV MASSIF: ARE SO-CALLED DIAMONDIFEROUS GNEISSES MAGMATIC ROCKS? - Massonne H.-J. (My University, 2003)
The petrography and chemical composition of minerals of quartz-rich diamondiferous rocks from the Kokchetav Massif, especially the zonation of garnet, were studied and compared with diamondiferous quartzofeldspathic rocks from the Saxonian Erzgebirge. Many compositional and textural features were found to be similar. For instance, microdiamonds are enclosed systematically in a specific intermediate growth zone of garnet in these rocks. On the basis of experimental data, a magmatic scenario was constructed to check if the quartz-rich diamondiferous rocks are of magmatic origin. By this, the P–T paths, derived here for the Kokchetav rocks, and the textural observations it is concluded that the minerals of the diamondiferous rocks have crystallized from silicate melts. These melts originated by anatexis of deeply submerged metasediments (Erzgebirge: at T as high as 1200°C, Kokchetav Massif: at 50–100°C lower T) and ascended from at least 200 km depth. Relics of the pre-anatectic evolution are still present, for instance, as garnet cores. After ascent and emplacement of the magma in deep portions of thickened continental crust (Kokchetav Massif: 45–50 km close to 800°C, Erzgebirge: 55–60 km at 30–50°C lower T) considerable quantities of (white and/or dark) micas formed by peritectic reactions from melt. For instance, garnets could be resorbed at this stage and biotite grew instead. After the magmatic stage, retrogression took place much stronger in the Kokchetav Massif. This was accompanied by deformation transforming broadly the magmatic texture of quartz-rich diamondiferous rocks from the Kokchetav Massif to a gneissic texture.